Parametric investigation of coconut shells as partial replacement of coarse aggregates in sustainable concrete - Arora Rishabh; Kumar Kaushal; Dixit Saurav; Kumar Tipu Rupesh; Kaul Padmini; Chauhan Swati; Kamala Raju Y.; Nijhawan Ginni; Haindavi P. (E3S Web of Conferences, 2023)
Sustainable construction materials for resource efficiency and environmental effect have grown in popularity .Coconut shells, a waste product of the coconut industry, are plentiful in tropical climates. They are lightweight and permeable, making them an attractive alternative to coarse aggregates. Coconut shells can reduce trash disposal and gravel and sand use by adding them to concrete mixtures. Coconut shell aggregates improve concrete’s mechanical strength and durability, although at a lesser rate than conventional aggregates. Coconut shell replacement depends on particle size, surface properties, and curing conditions. Coconut shells with concrete improve thermal insulation, density, and acoustics. In this investigation compressive and flexural strengths of Grade M20 has been studied by replacing natural coarse aggregates with coconut shells at 0%, 10%, 20% and 30% by weight at curing intervals of 7,14 and 28 days. Cubes and beams were casted and then tested and the tests revealed that coconut shells can be used upto 10% in replacement of natural aggregates imparting a strength almost equivalent to conventional concrete.